A CMIP5 multimodel projection of future temperature, precipitation, and climatological drought in China - Wang, Lin; Chen, Wen (International journal of climatology, 2014)
ABSTRACT In this study, fine‐resolution multimodel climate projections over China are developed based on 35 climate models and two emissions scenarios (RCP4.5 and RCP8.5) from phase five of the Coupled Model Intercomparison Project (CMIP5) by means of Bias Correction and Spatial Disaggregation. The yearly‐averaged temperature is projected to increase by 0.8 to 1.6 °C (0.8 to 1.7 °C), 1.5 to 2.7 °C (2 to 3.7 °C), and 1.9 to 3.3 °C (3.4 to 6 °C) under RCP4.5 (RCP8.5) in three time slices (2010–2039, 2040–2069, and 2070–2099), respectively. The most warming occurs in winter and the least in summer, and the inland areas in the northwest will warm much faster than the southeast. Under the background of surface warming, the probability of extreme low temperatures in winter defined as the monthly temperature being lower than the 9th percentile of the climatological distribution will sharply reduce to 0.1–1.7% under RCP4.5 for the period 2010–2039 and even lower for the following decades. For precipitation change, a remarkable increase is found over most areas of China except the Southwest, ranging from approximately 2 to 20%. The projected precipitation changes are highly robust in northern China, but inconsistent in southern China. In spite of widespread precipitation increases, most areas of China quantified by the Palmer Drought Severity Index are projected to become drier as a consequence of increasing evaporation driven by temperature increases. Detailed examination shows that drought that is moderate or severe according to current climate standards will become the norm in the future. Not only will incidences of severe and extreme drought increase dramatically in the future, but extreme wet events will also become more probable. Furthermore, the increasing drought risk in Southwest China and the Qinghai‐Tibetan Plateau is nearly twice that for other parts of China.